Analisis terhadap Penyelesaian Sengketa Konsumen di Indonesia Mengenai Ketidaksesuaian Label Produk Suplemen - Leonardo Halim; Ariawan Gunadi (Jurnal Hukum Lex Generalis, 2024)
Indonesia is a country that is still developing both in terms of education and also in terms of the economy. Indonesia as a country of law certainly has rules that apply in Indonesia and must be obeyed by all Indonesian people. The rules that apply in Indonesia are certainly for the good of Indonesia and also to advance the Indonesian state, especially in terms of the economy by regulating businesses that run in Indonesia. Of course, even though there are rules that specifically regulate businesses, namely the GCPL, there are still business actors who violate these provisions. The government's efforts in trade activities have made standardization that has been applied in the field of trade in Indonesia such as standardization of products, product identification, and others. Based on the case of protein milk, the government in maintaining the dispute is certainly by creating an institution, one of which is BPOM to maintain disputes over food and medicine. BPOM here is given the authority to issue product distribution permits and certificates with standards, BPOM can also conduct investigations in the field of drug and food control and can impose administrative sanctions on business actors who harm consumers. Consumer disputes in Indonesia are certainly one of the disputes that often occur in Indonesia and to resolve consumer disputes can be through BPSK. BPSK has the duty to handle and resolve consumer disputes through mediation, arbitration and conciliation. BPSK also has the authority to impose sanctions on business actors who have harmed their consumers. It can be concluded that with the existence of the GCPL there are still business actors who still oppose these rules. The author's suggestion is that the enforcement of consumer cases needs to be emphasized again because the enforcement of consumer cases is still lacking and some are even missed.